Upaya Meningkatkan Kemampuan Menulis Teks Laporan Observasi Keindahan Halaman Sekolah Dengan Menerapkan Metode Jigsaw - I Made Suparta; I Wayan Subaker (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This research is based on the fact that the ability to write report texts for class VIII B students of Tabanan 3 Public Junior High School for the 2022-2023 academic year is still below the minimum completeness criterion standard (KKM), which is 70.00. The score for the ability to write the text of the previous class VIII B observation report was 55.67%. The purpose of this study was to describe the ability to write texts based on observations about the beauty of the pages of Tabanan 3 Public Junior High School using the jigsaw method. This research is classified as classroom action research which consists of 2 cycles. The method used in collecting data is the observation method and the test method to measure the ability to write the observed text. The data obtained were analyzed by finding the average value score The results of the pre-cycle analysis obtained an average value of 55.67% while the average value of the first cycle obtained 68.67%. The percentage increase from pre-cycle to cycle I was 23.35%. In cycle II the average value obtained was 81.33%. The percentage increase from cycle I to cycle II was 18.44%.Thus, all 32 students in class VIII B of Tabanan 3 Public Junior High School were declared complete. In connection with the above it is suggested to Indonesian teachers in the teaching and learning process to use the jigsaw method, because with this method students' abilities have increased